The future of myelodysplastic syndrome—patient priorities and outcomes that matter - Poynton, Matthew; Gilmour-Hamilton, Catriona; Dale-Harris, Isabella; Clarke, Evelyn; Stanworth, Simon; Murphy, Mike; Roy, Noémi (Frontiers in Medicine, 2023)
Background Without a definitive curative option available to many patients, learning to live with myelodysplastic syndrome (MDS) and manage symptoms effectively becomes a priority in their care. Anaemia is an almost universal feature of MDS. Individuals suffer differently and better individualisation of care is needed. Most MDS patient information offers scant appreciation for disease heterogeneity, variable response to treatment and each patient’s likely trajectory. Methods We undertook a two-part, online workshop to discuss what matters most to people living with MDS. Patients generated questions about their condition which they felt should be addressed by research or change how their care is delivered. Patients voted on the importance of each topic, creating a “prioritised” list of issues. Results 14 participants of varying age and experience took part raising 56 unique questions under the themes of: Prognosis; End of life; Treatment; Supportive Care; Medical Staff Training; Diagnosis and Communication. These reflect the symptoms of MDS, improving quality of life (QoL) and communication. Discussion Although haemoglobin (Hb) levels have correlation to QoL, it is widely reported that other factors are important in determining QoL and need for transfusions varies despite stable Hb levels. We showed that Hb level and the need for transfusions is not comparable between different patients and even non-comparable over time meaning that the maximal benefit and timing of transfusions cannot be determined from Hb alone. This workshop highlighted patient dissatisfaction with the ‘numbers-led’ approach and the need for an alternative method to determine when to transfuse.